Fishermen and ICT: towards creating knowledgeable fishermen in Malaysia - Abu Hassan, Musa; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva; Omar, Siti Zobidah; Bolong, Jusang (American-Eurasian Network for Scientific Information, 2011)
The significant relationship between ICT and community development in Malaysia cannot be denied. Groups such as farmers, students, teachers, rural administrators and entrepreneurs have benefited a lot from the advantages that ICT offers. Besides this fact, do the fishermen as one of the major groups in Malaysia have benefited from ICT? This is a qualitative study and which used the data gained through literature and document analyses. Based on the analysis it was found that ICT development in Malaysia is well managed and planned. This can be seen through the establishment of several initiatives such as Rural Internet Center, Rural Info Center, National Information Technology Agenda and National Broadband Initiatives. Further analysis has discovered that there are a lot of benefits that fishermen could obtained through ICT. However, to ensure the fishermen will gain the benefits of ICT, a number of problems and obstacles related to ICT usage must be overcome.